STUDI TATA RIAS DAN BUSANA PENGANTIN LEGHA SUMENEP MADURA - Sulistiami sulis; Iut Nuraini (WAHANA, 2017)
Marriage isthe most sacred ceremony in the course of human life,each region hasits own proceduresperformed by tribes Madura in general and especially in the city Sumenep. Make up and bridalfashion become the center ofattention of the public and guests who attended the wedding,therefore,the bride would want to look attractive. Bridal Sumenep on each night receptionis dividedinto three kinds, namely legha bridal make up, bridal make up bridal make up kapotren and candles.The discussion on this matter is devoted to review of bridal legha. This research is motivated by thefact that Indonesia is actually rich variety harmoninasi customs in public life. The procedure foreachevent must be different tribe, one of the brides in East Java there that has a characteristicunique make up, among others Madura particularly Sumenep. Formulation of the problem in thisstudy is "How do makeup, fashion and bridal accessories legha Sumenep Madura?".The goal is todescribe the results of makeup, fashion and bridal accessories legha Sumenep Madura. Subjects inthis study consist edoffive people and the institutions, among others, the Department of TourismCulture Youth and Sports Sumenep, bridal make up expert legha Sumenep among others Drs.RMTaufiqurrahmanheisat the same legha bridal make up Sumenep cultural figures, Hj.Uhana bridalmake up artist and one of the members of the DPCHARPI MELATISumenepdistrict,Nuningmotherwhois also a bridal make up in Sumenep, as well as the male and female models areready make up legha bride. Data obtained by observation, interviews and documentation.